Analisis Faktor-Faktor yang Mempengaruhi Penggunaan layanan Mobile Banking pada Generasi Milenial - Dwi Melati, Jean Vania; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2024)
This research aims to identify factors that influence the use of mobile banking services in the millennial generation. Using a theoretical approach and literature review, this research explores various factors such as perceived trustworthiness, perceived security and privacy, perceived usability, feature availability and Social Influence. The results of literature analysis show that perceptions of trust and security and privacy are often considered important factors in the adoption of mobile banking by the millennial generation. In addition, perceived usefulness and availability of features and Social influence also play an important role although not always the main determining factors.